Singlet Fission in Carbene-Derived Diradicaloids - Ullrich, Tobias; Pinter, Piermaria; Messelberger, Julian; Haines, Philipp; Kaur, Ramandeep; Hansmann, Max M.; Munz, Dominik; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2020)
Herein, we present a new class of singlet fission (SF) materials based on diradicaloids of carbene scaffolds, namely cyclic (alkyl)(amino)carbenes (CAACs). Our modular approach allows the tuning of two key SF criteria: the steric factor and the diradical character. In turn, we modified the energy landscapes of excited states in a systematic manner to accommodate the needs for SF. We report the first example of intermolecular SF in solution by dimer self-assembly at cryogenic temperatures.
CRIS-Team WoS Importer:2020-04-07